Peran Sosio-Kultural dalam Pembentukan Karakter Anak Usia Dini: Telaah Literatur Interdisipliner - Syifa safitri (Jurnal Studi Pendidikan Anak Usia Dini, 2025)
The purpose of this research is to analyze socio-cultural factors in early childhood character building through an interdisciplinary literature review. A child's character development is strongly influenced by the social and cultural environment of the community in which they live, which includes the values, norms and practices that exist in society. This research brings together the developmental perspectives of psychology, sociology, anthropology and education to provide a holistic understanding of how socio-cultural factors influence the process of identity and character formation in the early stages of their lives. Based on the existing literature, it was found that interactions with family, school and community as well as the regulation of cultural norms are factors that influence the quality of social, emotional and cognitive development of AUD. The results of this study are expected to provide insights to educators, parents and stakeholders in formulating care and education strategies that pay more attention to the socio-cultural context so that children have better character.